1999
DOI: 10.1002/lt.500050513
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of liver transplant recipients on cyclosporine with renal impairment to mycophenolate mofetil

Abstract: The management of liver transplant recipients with renal function impairment remains controversial because cyclosporine withdrawal from triple immunosuppression regimens may be followed by graft rejection. A nonnephrotoxic and powerful immunosuppressant such as mycophenolate mofetil (MMF) could allow a reduction of cyclosporine dosage or its withdrawal and an improvement in renal function in these patients. Eleven patients with serum creatinine levels greater than 1.5 mg/dL, normal graft function, and a reject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
79
1
3

Year Published

2002
2002
2010
2010

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(89 citation statements)
references
References 25 publications
6
79
1
3
Order By: Relevance
“…In addition, we believe that patients with renal insufficiency should be considered for less nephrotoxic immunosuppressive regimens, including sirolimus and mycophenolate mofetil. 26,27 These drugs should be tested in controlled trials to determine safety and efficacy. In conclusion, approximately one third of patients undergoing OLT have evidence of pretransplant renal impairment.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we believe that patients with renal insufficiency should be considered for less nephrotoxic immunosuppressive regimens, including sirolimus and mycophenolate mofetil. 26,27 These drugs should be tested in controlled trials to determine safety and efficacy. In conclusion, approximately one third of patients undergoing OLT have evidence of pretransplant renal impairment.…”
Section: Discussionmentioning
confidence: 99%
“…38,39 However, withdrawal of cyclosporine therapy rarely improves renal outcome, although one study reported a slight improvement in renal function in patients successfully converted after 1 year to mycophenolate. 40,41 Furthermore, the added risk for rejection after cyclosporine therapy withdrawal is a major consideration before recommending this approach. Renal diagnoses other than cyclosporine toxicity leading to post-OLT ESRD include hemolytic uremic syndrome, immunoglobulin A (IgA) nephropathy, oxalosis, and membranoproliferative glomerulonephritis (MPGN).…”
Section: End-stage Renal Disease In the Liver Transplant Recipientmentioning
confidence: 99%
“…Previous experiences in LT recipients with renal functional impairment reported controversial results. In our experience, episodes of graft rejection were well controlled with an increase in CI, 10 but others have observed a poor responses. 12 In the present paper, two patients (18%) developed a rejection episode, both of which responded to increases in CI.…”
Section: Discussionmentioning
confidence: 51%
“…The use of MMF has allowed physicians to reduce cyclosporine exposure in LT recipients with renal functional impairment. 10 Some patients have been maintained on MMF monotherapy, but this strategy poses the risk of graft rejection. 11 The aim of the present study was to examine whether conversion to MMF for stable LT recipients with DM allows the reduction/withdrawal of CI and results in improve metabolic control.…”
Section: D Abetes Mellitus (Dm) Is a Frequent Metabolic Complicatiomentioning
confidence: 99%